Proprietários rurais do Distrito de Martinésia (Uberlândia-MG) : viver e permanecer no campo 1964-2005 - Silva, Renata Rastrelo e (2007)
Since the establishment of the military regime in Brazil in 1964, the countryside has become the target of modernizing policies, that is, among other things the State stimulated the acquisition of new technologies, the use of fertilizers and selected seeds. It tried to transform the technical basis of the activities of agriculture and cattle farming in Brazil by means of several instruments such as rural credit and minimum price policies. However, according to some scholars, such modernization was conservative , unequal , and painful as it favored the large producers to the detriment of the small ones, generating serious social costs such as the migration from countryside to city. Thus, several small land owners left the countryside because living there became something extremely hard and many others lost their lands due to debts owed to banks. In spite of this, several owners stayed in the countryside and my purpose here is exactly to analyze the strategies, the alternatives that made it possible for them to remain there until today. To understand such process I make a study of the rural land owners experiences in the area of the Martinésia district, municipality of Uberlândia, State of Minas Gerais, trying to analyze the reelaborations identified in their ways of living, working, having fun and relating to each other in order to stay in the countryside, (re)inventing their lives each day, struggling to keep their properties and to guarantee a way of living whose meaning transcends the mere possibility of making profits, as for many of them the land has the same value of life itself. In the present study, references such as Thompson and Williams were fundamental to the reflections on how people experience and interpret the transformations in their lives. In order to discuss such questions the main sources are the Jornal Correio, oral interviews, Atas do Conselho Comunitário Rural de Martinésia, statistical data, among others.